NGF Signaling Interacts With the Hippo/YAP Pathway to Regulate Cervical Cancer Progression - Wang, Lijun; Li, Jing; Wang, Rongli; Chen, He; Wang, Ruiqi; Wang, Wei; Yang, Xinyuan (Frontiers in Oncology, 2021)
Nerve growth factor (NGF) is increasingly implicated in cervical cancer progression, but its mechanism in cervical cancer is unclear. Here, studies demonstrate that NGF inhibits the Hippo signaling pathway and activates Yes-associated protein (YAP) to induce cervical cancer cell proliferation and migration. Our results suggested that stimulation of NGF promoted cell growth and migration and activated YAP in HeLa and C-33A cell lines. The expression of YAP target genes (CTGF and ANKRD1) was upregulated after NGF treatment. The NGF inhibitor Ro 08-2750 and siRNA-mediated NGF receptor gene silencing suppressed HeLa and C-33A cells proliferation and migration, activated large suppressor kinase 1 (LATS1) kinase activity, and suppressed YAP function. In addition, the expression of YAP target genes (CTGF and ANKRD1) was suppressed by Ro 08-2750 treatment in HeLa and C-33A cells. Interestingly, proliferation was significantly higher in NGF-treated cells than in control cells, and this effect was completely reversed by the YAP small molecule inhibitor-verteporfin. Furthermore, the mouse xenograft model shows that NGF regulates YAP oncogenic activity in vivo. Mechanistically, NGF stimulation inactivates LATS1 and activates YAP, and NGF inhibition was found to induce large suppressor kinase 1 (LATS1) phosphorylation. Taken together, these data provide the first direct evidence of crosstalk between the NGF signaling and Hippo cancer pathways, an interaction that affects cervical cancer progression. Our study indicates that combined targeting of the NGF signaling and the Hippo pathway represents a novel therapeutic strategy for treatment of cervical cancer.